Risk factors and conservative therapy outcomes of anastomotic leakage after gastrectomy: Experience of 3,926 patients from a single gastric surgical unit - He, Zhongyuan; Liu, Hongda; Zhou, Ling; Li, Qingya; Wang, Linjun; Zhang, Diancai; Xu, Hao; Xu, Zekuan (Frontiers in Oncology, 2023)
Background: Anastomotic leakage (AL) after gastrectomy is one of the severest postoperative complications and is related to increasing mortality. In addition, no consensus guideline about strategies of AL treatment has been established. This large cohort study aimed to inspect the hazard factors and efficacy of conservative treatment for AL in patients with gastric cancer. Methods: We reviewed the clinicopathological data of 3,926 gastric cancer patients undergoing gastrectomy between 2014 and 2021. Results contained the rate, risk factors and conservative therapy outcomes of AL. Results: In total, 80 patients (2.03%, 80/3926) were diagnosed with AL, and the esophagojejuostomy was the most frequent AL site (73.8%, 59/80). Among them, 1 patient (2.5%, 1/80) died. The multivariate analysis indicated that low albumin concentration(P=0.001), presence of diabetes(P=0.025), laparoscopic method(P<0.001), total gastrectomy(P=0.003) and proximal gastrectomy (P=0.002) were predicting factors for AL. The closure rate for conservative treatment of AL in the first month after AL diagnosis was 83.54% (66/79), and median time from leakage diagnosis to closure of leakage was 17 days (interquartile range 11-26 days). Low level of plasm albumin (P=0.004) was associated with late leakage closures. In terms of 5-year recurrence-free survival, no significant difference was observed between patients with and without AL. Conclusions: AL after gastrectomy is associated with albumin concentration, diabetes, the laparoscopic method and extent of resection. Conservative treatment is relatively safe and effective for the AL management in patients after gastric cancer surgery.